Exclusion is Forever: How Keeping Labour Rights Separate from Constitutional Rights Has Proven to Be a Bad Deal for American Trade Unions and Constitutional Law The Comparative Perspective - Hyde, Alan (Canadian Labour & Employment Law Journal, 2009)
Speaking from the U.S. experience, this paper argues that the exclusion of union speech, boycotts and picketing from constitutional protection has been harmful for labour and for the U.S. Constitution. The author points out that in recent decades the scope of speech that is protected under the First Amendment has expanded significantly, and now includes consumer boycotts, "symbolic speech" that combines con- duct and communication, and even threatening speech. All of these rights of expression are denied to unions, supposedly on the ground that labour rights should be, and are, regulated through a comprehensive administrative scheme. In the author's view, howeve, that scheme has become ossified, and has completely failed to keep up with developments in First Amendment law. As a result, union speech and action is uniquely disfavoured: flag-burning, cross-burning and the St. Patrick's Day parade are constitutionally protected forms of expression, but union picketing is not. Canadians, then, when considering a constitutional right to strike, should be wary, of the argument that the regulation of such a right is better assigned to administrators rather than the courts.